RELAÇÃO DO POLIMORFISMO DO GENE FTO COM A OBESIDADE EM ADOLESCENTES. - RODRIGUES, Liliane dos Santos (2019)
Obesity is characterized as a nutritional disorder that is related to excess body adiposity, as chances of developing chronic noncommunicable diseases such as diabetes mellitus, dyslipidemia and hypertension. The individual's environment and / or lifestyle, differentiated diet and genetic basis contribute to the development of multifactorial dysfunction. Thus, the objective of this study was to investigate the relationship of an FTO gene polymorphism with obesity in adolescents from São Luís, Maranhão, Brazil. This study was carried out with adolescents aged 18 to 19 years in the RPS Cohort of the city of São Luís - MA. The case was made by 378 obese adolescents and the control by 378 non-obese. Obesity was evaluated using the percentage of Body Fat (% GC) measured by air displacement plethysmography technique. The variables together are the socioeconomic, demographic, lifestyle, physical activity, waist circumference (WC), circulation-stature rate (RCE) and Body Mass Index (BMI). Blood samples were collected for genomic DNA extraction, such as the real-time PCR technique, the rs9939609 polymorphism of the FTO gene. A statistical analysis was performed in the STATA14.0 program. The variables were compared between groups using the Chi-Square test. The Hardy-Weinberg equilibrium was calculated for the study sample. Normality of the anthropometric measurements BMI, CC, RCE and% GC were obtained by the Shapiro-Wilk test. The Kruskall-Wallis test was used to compare the anthropometric measurements with the different polymorph genotypes. Just as the variable sex, age and adventure, the physics of teaching statistically between the groups under study (p <0.001). Regarding the genetic data, the results indicated that the population is in Hardy-Weinberg equilibrium (p = 0.0515). The difference was statistically significant between the genotypic (p = 0.719) and allelic frequencies (p = 0.812) in relation to the case and control groups. Regarding the anthropometric measures, no significant differences were also found in relation to the different genotypes (AA, AT and TT). Thus, it was concluded that sample sampling is not a combination of the presence of the risk genotype with the objective of developing a group of adolescents.